Biological activities and physiochemical properties of low-fat and high-fat coconut-based kefir - Taleb Abadl, Muna Mahmood; Mohsin, Aliah Zannierah; Sulaiman, Rabiha; Abas, Faridah; Muhialdin, Belal J.; Meor Hussin, Anis Shobirin (Elsevier, 2022)
Coconut milk is a rich source of several nutrients and free of lactose which can be an excellent alternative to cow milk for lactose-intolerant consumers. This study aimed to investigate the potential of producing coconut-based kefir beverages using low-fat and high-fat coconut milk. The beverage was evaluated for pH values, titratable acidity, peptide content, antibacterial activity, antioxidant activity, and rheological properties. The results showed a significant increase in lactic acid bacteria and yeast after the fermentation for 24 h. The pH of the low-fat and high-fat coconut milk kefir declined to 3.77 ± 0.01 and 3.84 ± 0.01, respectively. The titratable acidity increased to 0.75 ± 0.04% and 0.66 ± 0.01% lactic acid, respectively. The fermentation with kefir grains significantly increased the peptides content of low-fat coconut milk to 0.7 ± 0.016 mg mL−1, and for high-fat coconut milk, it increased to 0.571 ± 0.038 mg mL−1. In addition, low-fat coconut kefir showed strong antibacterial growth inhibition and antioxidant activity. The apparent viscosity of the kefir beverage decreased with increasing shear rate and was higher at a lower temperature. The low-fat coconut kefir's flow behavior index (n) and consistency index (K) were 0.216 and 0.223. The consistency index (K) was 3.067 and 0.576 Pa s n at 5 and 25 °C, respectively. Moreover, the (n) values of high-fat coconut kefir were recorded as 0.422 and 0.581, and (K) values as 0.33 and 1.245 Pa s n. Therefore, low-fat coconut milk can be an alternative to cow milk in producing kefir-based beverages.